Manajemen Rhinitis Alergi - Salsabila Dwi Irga Syarif; Mukhlis Imanto; Septia Eva Lusiana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Allergic rhinitis (AR) is an atopic disease characterized by symptoms of nasal congestion, clear rhinorrhea, sneezing, postnasal drop, and nasal pruritis. The disease affects one in six people and is associated with significant morbidity, loss of productivity, and health care costs. Historically, AR was considered a disease process in the nasal airways only, although it is not serious, allergic rhinitis should be considered as a quite serious condition because it can affect the sufferer's quality of life due to the severity of the symptoms experienced and can also cause various complications. However, the development of integrated airway theory has classified AR as a component of the systemic allergic response, with other related conditions, such as asthma and atopic dermatitis, having an underlying systemic pathology. Even though it is not serious, allergic rhinitis should be considered as a quite serious condition because it can affect the sufferer's quality of life due to the severity of the symptoms experienced and can also cause various complications. In addition to nasal symptoms, patients with AR may also experience allergic conjunctivitis, non-productive cough, Eustachian tube dysfunction, and chronic sinusitis. Once diagnosed, AR can be treated in a variety of ways, with intranasal glucocorticoids being the first line of therapy.